Genomics reveals the role of admixture in the evolution of structure among sperm whale populations within the Mediterranean Sea - Violi, Biagio; de Jong, Menno J.; Frantzis, Alexandros; Alexiadou, Paraskevi; Tardy, Céline; Ody, Denis; de Stephanis, Renaud; Giménez, Joan; Lucifora, Giuseppe; Silva, Mónica A. e; Oliveira, Cláudia; Alves, Filipe; et al. (Molecular Ecology, 2023)
In oceanic ecosystems, the nature of barriers to gene flow, and the processes by which populations may become isolated are different from the terrestrial environment, and less well understood. In this study we investigate a highly mobile species (the sperm whale, Physeter macrocephalus) that is genetically differentiated between an open North Atlantic population and the populations in the Mediterranean Sea. We apply high resolution single nucleotide polymorphism (SNP) analysis to study the nature of barriers to gene flow in this system, assessing the putative boundary into the Mediterranean (Strait of Gibraltar and Alboran Sea region), and including novel analyses on structuring among sperm whale populations within the Mediterranean basin. Our data support a recent founding of the Mediterranean, around the time of the last glacial maximum, and show concerted historical demographic profiles in both the Atlantic and in the Mediterranean. In each region there is evidence for a population decline around the time of the founder event. The largest decline was seen within the Mediterranean Sea where effective population size is substantially lower (especially in the eastern basin). While differentiation is strongest at the Atlantic/Mediterranean boundary, there is also weaker but significant differentiation between the eastern and western basins of the Mediterranean Sea. We propose, however, that the mechanisms are different. While post-founding gene flow was reduced between the Mediterranean and Atlantic populations, within the Mediterranean an important factor differentiating the basins is likely a greater degree of admixture between the western basin and the North Atlantic and some level of isolation between the western and eastern Mediterranean basins. Subdivision within the Mediterranean Sea exacerbates conservation concerns and will require consideration of what distinct impacts may affect populations in the two basins. 1,96 6,622 Q1 Q1 SCIE 11,0